AL-KALAM AL-KHOBARI FI SURAH YUSUF (DIRASAH TAHLILIYAH BALAGHIYAH) - Aini choirunnisa, Eshas; Azhari, Faiz; Yulianti, Yulianti (Sekolah Tinggi Ilmu Adab dan Budaya Islam Riyadul 'Ulum, 2021)
Understanding the science of balaghah for Muslims if they want to know and understand that i'jaz of the Qur'an is important. Kalam Alkhabari is one of the materials that must be understood because if we want to understand the purpose of Kalam alkhabari which is in the verses of the Qur'an except by Balagha analysis. Therefore, this research has 3 objectives; 1. To know the verse containing Kalam alkhabari in Surah Yusuf 2. To know the kinds of Kalam alkhabari in Surah Yusuf 3. To know the purpose of Kalam alkhabari contained in Surat Yusuf. The analytical descriptive qualitative is employed in this research. The object of study in this study is kalam Alkhabari in Surat Yusuf. The data sources in the study are divided into primary resources, namely the Qur'an Al Karim and secondary data sources, namely books related to the title of the study. The documentation method was used in collecting the data. This study showed show that in 25 verses in Surat Yusuf there are 43 Kalam alkhabari consisting of 24 kalam alkhabari Al ibtidai, 12 kalam thalaby, and 7 kalam inkary